The impact of supplementation with pomegranate fruit (Punica granatum L.) juice on selected antioxidant parameters and markers of iron metabolism in rowers - Urbaniak, A.; Basta, P.; Ast, K.; Woloszyn, A.; Kurianska-Woloszyn, J.; Latour, E.; Skarpanska-Stejnborn, A. (Journal of the International Society of Sports Nutrition, 2018)
Background: The aim of this study was to analyse the effect of pomegranate juice (POM) supplementation on the levels of selected pro-inflammatory cytokines, hepcidin and markers of iron metabolism in well-trained rowers. Method: The double-blind placebo-controlled study included 19 members of the Polish Rowing Team. The athletes were randomised into the supplemented group (n = 10), receiving 50 ml of standardised POM daily for two months, or the placebo group (n = 9). The subjects performed a 2000 m test on the rowing ergometer at the start of the project (baseline) and end of follow-up period. Blood samples from the antecubital vein were obtained three times during each trial: prior to the exercise, one minute after the test, and following a 24 h recovery. Results: The study documented the beneficial effect of supplementation with pomegranate fruit juice on TAC (P < 0.002). During the resting period, TAC level in the supplemented group was significantly higher than in the placebo group (x ± SD, 2.49 ± 0.39 vs. 1.88 ± 0.45, P < 0.05). The ergometric test conducted at baseline demonstrated a significant post-exercise increase in the concentrations of soluble transferrin receptors (P < 0.04), iron (P < 0.002) and IL-6 (P < 0.02), and to a significant post-exercise decrease in TAC. A significant increase in IL-6 concentration was also observed 24 h post-exercise. The exercise test conducted at the end of the follow-up period resulted in a significant decrease in TBIC and a significant increase in UIBC (P < 0.001), observed in both groups, both immediately post-exercise and after the resting period. Conclusion: Supplementation with POM contributed to a significant strengthening of plasma antioxidant potential in the group of well-trained rowers, but had no effect on iron metabolism markers.